Description of the aberrant Leptopilina lasallei n. sp., with an updated phylogeny of Leptopilina Förster (Hymenoptera: Figitidae: Eucoilinae). Issue 9 (18th March 2020) - Buffington, Matthew L.; Giorgini, Massimo; Lue, Chia-Hua; Formisano, Giorgio; Cascone, Pasquale; Forshage, Mattias; Driskell, Amy; Guerrieri, Emilio
ABSTRACT: In the search for native Asian parasitoids of Drosophila suzukii, the notorious spotted-wing Drosophila (SWD), an odd new species of Eucoilinae was discovered. Leptopilina lasallei sp. nov . is herein described and diagnosed relative to other eucoilines associated with drosophilid hosts. Morphologically, L. lasallei is somewhat aberrant within Leptopilina ; phylogenetically, L. lasallei is sister group to the core Leptopilina . In the process of investigating L. lasallei, a de novo molecular phylogeny of Leptopilina was generated and is included here. The integrated approach used for the characterisation of L. lasallei, and the resulting phylogeny of Leptopilina, produced data useful to select parasitoid species for SWD biological control.http://www.zoobank.org/urn:lsid:zoobank.org:act:402D504A-4616-4524-85D7-1C13A6276F06 http://www.zoobank.org/urn:lsid:zoobank.org:act:402D504A-4616-4524-85D7-1C13A6276F06